2005
DOI: 10.1093/annonc/mdi187
|View full text |Cite
|
Sign up to set email alerts
|

Second-line (post-study) chemotherapy received by patients treated in the phase III trial of pemetrexed plus cisplatin versus cisplatin alone in malignant pleural mesothelioma

Abstract: PSC in malignant pleural mesothelioma was significantly associated with prolonged survival. It is not known whether the reduced risk of death was associated with PSC or whether patients who had prolonged survival tended to receive more PSC. The pemetrexed plus cisplatin treatment group had a statistically significant survival advantage even though fewer patients from that arm of the trial received PSC. The potentially beneficial role of PSC should be assessed in prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(79 citation statements)
references
References 17 publications
3
74
0
2
Order By: Relevance
“…Immortal time bias [16] poses another problem in nonrandomised studies as survival is calculated from day of diagnosis and, by definition, chemotherapy patients cannot die between diagnosis and their first cycle, hence getting a survival head start. The latter bias may also explain why survival appears to be better for patients who receive post-study chemotherapy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Immortal time bias [16] poses another problem in nonrandomised studies as survival is calculated from day of diagnosis and, by definition, chemotherapy patients cannot die between diagnosis and their first cycle, hence getting a survival head start. The latter bias may also explain why survival appears to be better for patients who receive post-study chemotherapy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Transl Lung Cancer Res 2017;6(3):295-314 tlcr.amegroups.com chemotherapy had a statistically prolonged survival with an adjusted hazard ratio of 0.56 (CI: 0.44-0.72), demonstrating benefit of additional systemic therapy after first line treatment (65). Prior to cisplatin and pemetrexed becoming the first-line standard of care, Jassem et al showed that pemetrexed increased progression free survival in previously treated, pemetrexed-naĂŻve patients (66).…”
Section: Nd Line and Salvage Therapymentioning
confidence: 98%
“…Indirect data extracted from the follow-up of a first-line randomised trial [64] suggested that second-line chemotherapy after cisplatin-pemetrexed could increase survival in comparison with symptomatic treatment alone. These data need confirmation in a randomised study.…”
Section: Chemotherapy Of Mpmmentioning
confidence: 99%